2021
DOI: 10.3390/ijerph19010123
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors for Progression to Diabetes Mellitus: A Retrospective Cohort Study

Abstract: (1) Objective: This study examined the incidence and risk factors contributing to the progression to diabetes mellitus (DM) in a seven-year follow-up study of non-diabetic National Health Examinees. (2) Methods: For this retrospective observational cohort study, we used two national representative databases: the National Health Screening (HEALS) database 2009 and the National Health Insurance Service (NHIS) database 2009–2015. The eligible subjects without DM with blood sugar levels of <126 mg/dL were selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Sharma et al in a study in Mumbai, India reported an incidence rate of 5.3 cases per 1000 person-years 28 . In a study conducted in Korea, Hyun et al reported a higher incidence rate of 22.8 per 1000 person-years for DM 22 . Similarly, Rojo-Martínez et al observed an adjusted overall incidence rate of 11.6 per 1000 person-years in Spain 29 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Sharma et al in a study in Mumbai, India reported an incidence rate of 5.3 cases per 1000 person-years 28 . In a study conducted in Korea, Hyun et al reported a higher incidence rate of 22.8 per 1000 person-years for DM 22 . Similarly, Rojo-Martínez et al observed an adjusted overall incidence rate of 11.6 per 1000 person-years in Spain 29 .…”
Section: Discussionmentioning
confidence: 98%
“…Diabetes is a chronic disease 6 influenced by various factors. Older age 8 , 21 , female sex 22 and high BMI 6 , 23 are among the major risk factors for the development of DM. Despite extensive research in this field, it remains crucial to gain a better understanding of disparities in risk factor profiles and the burden of diabetes across different populations 6 .…”
Section: Introductionmentioning
confidence: 99%
“…develop diabetes than those with normoglycemia (32.5 vs. 7.2%) 13 . A 6-year Korean observational cohort study demonstrated that 21.9% of the IFG group progressed to diabetes, compared to 14% in the normoglycemic population 14 . In addition, statin use is associated with NODM occurrence, and the risk of NODM occurrence increases by 12-61% when using statins compared to the non-statin use group, depending on the study and statin type [15][16][17] .…”
Section: Declarationsmentioning
confidence: 99%
“…Diabetes places a significant burden on society in the form of increased medical costs, lost productivity, premature mortality, and intangible costs such as decreased quality of life ( 14 ). Currently, smoking, high-risk drinking, dyslipidemia, hypertension, and metabolic syndrome were reported as the risk factors for diabetes ( 15 ). However, a few studies have explored the relationship between salt and sodium intake and diabetes, and the results have shown inconsistency ( 16 18 ), and no studies have looked at the relationship between sodium intake and diabetes in a specific group of people without hypertension.…”
Section: Introductionmentioning
confidence: 99%